The Return of Embodied Energy Invested in Domestic Solar Water Heating Systems - Kalogirou, Soteris A. (My University, 2004)
In this paper the environmental protection offered by domestic solar water heating systems is presented. By using solar energy considerable amounts of greenhouse polluting gasses are avoided. The savings, compared to a conventional system, are about 80%, with electricity or diesel backup and about 75% with both electricity and diesel backup. Additionally, all systems investigated give positive and very promising financial characteristics. With respect to life cycle assessment of the systems, the energy spent for the manufacture and installation of the solar systems is recouped in about 1.2 years, whereas the payback time with respect to emissions produced from the embodied energy varies from a few months to 3.7 years according to the fuel and the particular pollutant considered. It is therefore concluded that solar systems offer significant benefits and should be employed whenever possible in order to achieve a sustainable future.
Keywords: Environmental protection; Solar water heating; Solar energy